Dynamics of Ethnic Conflict Among the Hamer, Nyangatom, and Dassanech in Ethiopia’s South Omo Zone: The Struggle Communities for Land - Shetahun, Asmare (RAHMATAN LIL ALAMIN: Journal of Peace Education and Islamic Studies, 2025)
This study investigates the nature and dynamics of land-related conflicts in the Hamer, Nyangatom, and Dassanech communities of South Omo, Ethiopia, with a specific emphasis on conflict management mechanisms and the growing impact of economic pressure and climate change. Employing a qualitative case study design, the research reveals that land disputes remain a persistent threat to community cohesion, socio-economic development, and intergroup relations. These conflicts are largely driven by competing claims over scarce natural resources—including grazing land, water points, and agricultural land—resources which have become increasingly limited due to prolonged droughts and climate variability. At the core of the disputes lies a tension between exclusive resource control and equitable resource sharing. The transboundary nature of some resource competitions further exacerbates the conflict. Rather than showing signs of resolution, these conflicts have evolved into cyclical and seasonal patterns of violence. The findings suggest that strengthening justice systems, institutional frameworks for conflict resolution, and community-based peacebuilding initiatives—particularly those integrating climate adaptation, early warning systems, and livelihood diversification—are critical to mitigating conflict and fostering long-term stability in the region.